Characterization of plant growth-promoting bacteria from kacip fatimah (Labisia pumila Benth. & Hook. f.) and its effects on growth of the plant - Awang, Yasmi (2015)
Kacip Fatimah (Labisia pumila) is one of the major medicinal plant species in Malaysia. Mass production of this plant is difficult as it grows very slow under cultivated condition. Plant growth-promoting bacteria (PGPB) are associated with many plant species and commonly present in many environments. These beneficial rhizosphere organisms in Kacip Fatimah could improve the plant growth and its phytochemical properties. A series of experiments were conducted in laboratory and glasshouse conditions with the following objectives; (i) to isolate and characterize the beneficial traits of plant growth-promoting bacteria (PGPB) isolated from Kacip Fatimah (Labisia pumila) established under natural forest, (ii) to evaluate the effects of PGPB on growth and chemical properties of Kacip Fatimah (Labisia pumila) under glasshouse conditions, and (iii) to determine the effects of PGPB on Kacip Fatimah (Labisia pumila) root colonization. Bacterial populations from Kacip Fatimah plants sampled from two natural forest sites were determined on nutrient agar (NA) media plates and screened for plant growth promoting traits. Two promising bacterial isolates were subjected to partial sequence polymerase chain reaction (PCR) identified as Stenotrophomonas sp. and Exiguobacterium sp. were chosen for the plant inoculation study in glasshouse condition. Two varieties of 2 months old Kacip Fatimah plants were planted in 14’ x 14’ polybag containing mixed cocopeat, rice husk and chicken dung at the ratio of 5:5:1. The experiment was laid out in a Completely Randomized Design (CRD) with five replications. The bacterial populations differed among plant parts and varieties. In L. pumila var. alata, high bacterial population was found in the phyllosphere and low in root endosphere. In contrast, L. pumila var. lanceolata, showed higher population in root endosphere and low in phyllosphere. The Gram reaction showed that 12 isolates were Gram-negative and 25 were Gram-positive. All bacteria were able to grow on N-free solid malate medium except two of the isolates. Thirteen of the isolates were able to solubilize calcium phosphate. Six of the isolates were positive for carboxymethylcellulase (CMC) and citrus pectin test. Only one of the isolate showed positive for both carboxymethylcellulase (CMC) and negative for citrus pectin. Most of strains were able to produce indole-acetic acid (IAA). Twenty-four of the isolates showed positive result for catalase test and 22 isolates showed positive result for starch hydrolysis. There were some differences in the plant growth parameters with bacterial inoculation. Inoculation of PGPB seems able to affect the growth of Kacip Fatimah for both of var. lanceolata and var. alata under glasshouse. Exiguobacterium sp.increased bacterial populations in rhizosphere and stem endosphere of var. alata, increased flavonoid content and enhanced stomatal conductance of var. lanceolata. Stenotrophomonas sp. influenced transpiration rate and stomatal conductance and bacterial population in non-rhizosphere of var. alata, improved leaf width of var. lanceolata and increased stem diameter and bacterial population in root endosphere of both varieties. Dual inoculation influenced Kacip Fatimah growth as it increased leaf length and leaf width of var. alata, transpiration rate and water vapor deposit of var. lanceolata, total phenolic content and photosynthesis rate for both varieties. There were no significant difference in root biomass, shoot biomass and leaf area index of Kacip Fatimah plants with the bacterial inoculations. Scanning Electron Microscope (SEM) observations revealed the ability of the bacterial isolates to colonize the root surface. In general, plant growth-promoting bacteria isolated from Kacip Fatimah were able to give effects on the growth of the plant through several growth promoting traits.